2002
DOI: 10.1017/s0033291701004962
|View full text |Cite
|
Sign up to set email alerts
|

The clinical epidemiology of hysteria: vanishingly rare, or just vanishing?

Abstract: Vanish 1. intr. To disappear from sight or become invisible, esp. in a rapid and mysterious way (Shorter Oxford English Dictionary, 1972).There is a well-known view that hysteria has virtually disappeared in the Western world. There are two versions of this argument: one is that there was never a clinical disorder that coincided with the diagnosis, and hysteria has now been reconstructed as something else (e.g. Micale, 1993). The other is that hysteria did exist but has now become much rarer than it was (most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Our study indicates that conversion disorder is less common in children than in adults where incidence rates of 5-12 per 100 000 have been reported. 7 The higher incidence in adults could be related to the role of trauma in the pathogenesis of conversation disorder, 8 such that the cumulative effect of trauma in the journey from childhood to adulthood would increase the risk. It might also be related to developmental immaturity, since we, as in previous studies, 2 found the incidence to be lower in the younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that conversion disorder is less common in children than in adults where incidence rates of 5-12 per 100 000 have been reported. 7 The higher incidence in adults could be related to the role of trauma in the pathogenesis of conversation disorder, 8 such that the cumulative effect of trauma in the journey from childhood to adulthood would increase the risk. It might also be related to developmental immaturity, since we, as in previous studies, 2 found the incidence to be lower in the younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that the limited number of epidemiological investigations into hysteria has contributed to the impression that this remains a rare phenomenon. 100 The major cultural change to impact on war syndromes in the last quarter of the twentieth century appears to be a general fear of toxins spread as a result of modern industrial life. Of the 218 Gulf War veterans in our study who gave an explanation, 34.3 per cent believed that their condition was caused by some form of poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…Several prognostic risk factors have been identified, such as the duration of symptoms, the presence of psychiatric and medical co-morbidity, and poor social life perception (Thomas, Vuong, & Jankovic, 2006). The prevalence is estimated to be as high as 50 per 10,0000, with an over-representation of women (Akagi & House, 2002).…”
Section: De Letter Et Almentioning
confidence: 99%